2019
DOI: 10.1007/s13197-019-03900-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Cistus incanus L. leaves on wheat pasta quality

Abstract: Modern nutritional trends and looking for functional food and dedicated products for various consumers are a source of inspiration for scientists to develop new pro-health supplemented foods with high quality. Therefore, the present study aimed to determine the selected properties of common wheat pasta fortified with dried Cistus incanus in amount from 1 to 5% as a replacement of wheat flour. Pasta was made with a spaghetti shape and dried. Supplemented pasta was tested for total phenolics content, the total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
(61 reference statements)
12
30
1
Order By: Relevance
“…Above this value, Fc decreased. A similar tendency was observed by Lisiecka et al [33] when Cistus incanus L. leaves were added to common F c of cooked pasta ranged from 0.42 N to 0.56 N. It was observed that the addition of dried banana up to 3% did not have a significant influence on F c . Above this value, F c decreased.…”
Section: Cutting Forcesupporting
confidence: 84%
See 1 more Smart Citation
“…Above this value, Fc decreased. A similar tendency was observed by Lisiecka et al [33] when Cistus incanus L. leaves were added to common F c of cooked pasta ranged from 0.42 N to 0.56 N. It was observed that the addition of dried banana up to 3% did not have a significant influence on F c . Above this value, F c decreased.…”
Section: Cutting Forcesupporting
confidence: 84%
“…However, significant changes were observed only between CP and PB2, PB3, PB4 and PB5. The reduction in the intensity of the yellow colour of the cooked pasta may be due to the swelling of the pasta and the conversion of pigments, thereby causing a decrease in yellowness during cooking [33]. For cooked pasta, TDC was significantly increased with the addition of BP (from 1.44 to 9.70).…”
Section: Colour Parametersmentioning
confidence: 99%
“…Till date, no research has been conducted to determine the effect of dried CI leaves on bread characteristics. We are the first to carry out such a study with CI leaves; moreover, similar findings were reported for pasta supplemented with CI leaves [22]. However, the proportion of this additive should not exceed 3%, as it results in a change of sensory characteristics.…”
Section: Sensory Evaluation Of Bread Enriched With Cistus Incanus L supporting
confidence: 73%
“…The least OHradical scavenging activity and chelating power (CHEL) was observed for control bread, whereas these activities increased with increasing concentrations of CI in the formulated bread recipe. A few other studies confirmed the antioxidative potential of CI when included as a functional additive to pasta [22]. Antioxidative potential of bread was also improved by green tea powder, herbs, and tomato paste [19].…”
Section: Total Phenolic Content and Antioxidant Activity Of Bread Incmentioning
confidence: 84%
See 1 more Smart Citation